2022
DOI: 10.3389/fmed.2022.884679
|View full text |Cite
|
Sign up to set email alerts
|

Small Airways: The “Silent Zone” of 2021 GINA Report?

Abstract: Asthma is a chronic disease, affecting approximately 350 million people worldwide. Inflammation and remodeling in asthma involve the large airways, and it is now widely accepted that the small airways (those with an internal diameter <2 mm) are involved in the pathogenesis of asthma and are the major determinant of airflow obstruction in this disease. From a clinical perspective, small airways dysfunction (SAD) is associated with more severe bronchial hyperresponsiveness, worse asthma control and more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
1
5
1
Order By: Relevance
“…These results are consistent with other published data, in which asthma control was closely related to SAD and clinical phenotypes associated with SAD [ 8 , 11 , 21 27 ]. Notably, in the majority of these studies, the IOS is better associated with asthma control than spirometry, supporting the importance of using IOS and more modern tools in addition to spirometry in the evaluation of asthma control.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with other published data, in which asthma control was closely related to SAD and clinical phenotypes associated with SAD [ 8 , 11 , 21 27 ]. Notably, in the majority of these studies, the IOS is better associated with asthma control than spirometry, supporting the importance of using IOS and more modern tools in addition to spirometry in the evaluation of asthma control.…”
Section: Introductionsupporting
confidence: 93%
“…Many studies and systematic reviews have suggested that small airway dysfunction (SAD) is associated with more severe bronchial hyper-responsiveness, worse asthma control and a higher number of exacerbations [ 4 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma is a frequent long-term respiratory condition that impacts over 350 million individuals globally (Cottini et al 2022 ). Over the past decades, the incidence and prevalence of asthma have increased, especially in children.…”
Section: Introductionmentioning
confidence: 99%